The Granta book of the African short story - Habila, Helon 1967- (Granta Publications, 2012)
The Granta Book of the African Short Story introduces a group of African writers described by its editor, Helon Habila, as 'the post-nationalist generation'. Introducing a diverse and dazzling collection from all over the continent - from Morocco to Zimbabwe, Uganda to Kenya - Habila has focused on younger, newer writers, interspersed with some of their older, more established peers, to give a fascinating picture of a new and more liberated Africa. Disdaining the narrowly nationalist and political preoccupations of previous generations, these writers are characterized by their engagement with the wider world and the opportunities offered by the internet, the end of apartheid, the end of civil wars and dictatorships, and the possibilities of free movement around the world. Many of them live outside Africa. Their work is inspired by travel and exile. They are liberated, global and expansive. As Dambudzo Marechera wrote: "If you write for a particular nation, or tribe, then f*** you." These are the stories of a new Africa, punchy, self-confident and defiant. Final selection includes: Rachida El Charni; Henrietta Rose-Innes; George Makana Clarke; Ivan Vladislavik; Mansoura Ez Eldin; Rogerio Mandjate; Aminatta Forna; Igoni Barrett; Patrice Nganang; Leila Aboulela; Petina Gappah; Ala Al-Aswany; Doreen Baingana; EC Osondu Other writers that may appear include: Olufemi Terry; Abdourahman Waberi; Alain Mabanckou; Veronique Tadjo; Ungulani Ba Ka Khosa; Jean-Luc Raharimanana; Leila Lalami; Milly Jafta; Manuel Rui; Uwem Akpan; Chimamanda Adichie; Zoe Wicombe; Phaswane Mpe; Diane Awerbuck; Ondjaki; Dambudzo Marechera; Camara Laye; Alex La Guma; Brian Chakwava; Ala Al-Aswany; Tahar Ben Jelloum; Yvonne Vera; Monica Arac; Abdulrazak Gurnah; Niq Mhlongo; Fatou Diome; Biyi Bandele; Ben Okri; Tayeb Salih.